Efecto del extracto crudo de frutos frescos de Vaccinium corymbosum “arándano” en Rattus norvegicus var. albinus con hiperglicemia inducida - Reyes Gil, Verónica Lisette (2017)
The objective of this research was to determine the effect of the fresh extract of the fresh fruits of Vaccinium corymbosum "blueberry" in Rattus norvegicus var. albinus with induced hyperglycemia. For this, the fruits were selected, washed and crushed, filtered and the cranberry extract was obtained. We worked with 28 male specimens of 4 months of age with a weight between 300-350g randomly distributed in 4 groups of 7 specimens each: white group (0.9% physiological saline at a dose of 5mL / kg of body weight for 15 days orally), control group (Induction of hyperglycemia with alloxan at a dose of 75mg / kg and treatment with 0.9% physiological saline at a dose of 5mL / kg for 15 days), problem group 1 and 2 (Induction of hyperglycemia with alloxan at a dose of 75mg / kg and treatment with cranberry extract at doses of 40mg / kg and 80 mg / kg respectively for 15 days). The glycemia was taken before the start of the study (baseline values), at the end of the hyperglycemia induction and at the end of the treatment, using the Accu-Chek® softclix glucometer. The results show that the glycaemia decreased significantly after the treatment with the bilberry extract (p <0.05), for the problem group 1 of 364.57 ± 30.72 mg / dL decreased to 218.00 ± 11.25 mg / dL and for the problem group 2 of 373.86 ± 9.31 mg / dL decreased to 158.14 ± 20.33 mg / dL. It is concluded that the crude extract of fresh fruits of Vaccinium corymbosum at doses of 40mg / kg and 80mg / kg decreases blood glucose levels in Rattus norvegicus var. albinus with induced hyperglycemia, presenting a greater decrease in glycemia in the dose of 80 mg / kg of raw bilberry extract